Douglas R. Fisher papers - Fisher, Douglas R.
Typewritten transcript of Fisher's oral testimony, given in the 1960s, of his World War II service in the Philippines and of years as a Japanese prisoner of war, 1942-1945. Includes postcards (1942-1945) concerning his status and health as a prisoner, photocopy of a list of officers transported in 1945, and newspaper clipping.
U.S. naval officer.
Collection material in English.
Forms part of: Naval Historical Foundation collection.
Keywords: Prisoners of war -- Japan; Prisoners of war -- United States; World War, 1939-1945 -- Prisoners and prisons; World War, 1939-1945 -- Philippines; Naval officers